RANCANG BANGUN MESIN ROASTING DI IKM REPUBLIK TANI MANDIRI - Yuswono Hadi; Adam Edward Widiamsa (Jurnal Rekayasa Mesin, 2022)
This study aims to determine the design of the roasting machine according to the needs of small business (IKM), IKM Republik Tani Mandiri is a small businesses engaged in processing coffee beans in Kucur Village. This research is focused on increasing production capacity by designing a roaster machine. Research methods The method used is Quality Function Deployment (QFD) phase 1 and product planning and development methods in determining the design of the roasting machine according to the needs of IKM. The calculation of the QFD method that has been carried out will be used to determine the concept of a roasting machine design with product planning and development methods. The design concept can be identified as follows: a gas burner, a rectangular engine cover, a manual temperature gauge, a 3-5kg tube volume, and a two-way dynamo. In the design of the roasting machine, it can be seen that in one roasting cycle with a capacity of 5 kg it takes 40 minutes, while the old machine takes 210 minutes, resulting in a 525% increase in capacity.